Murder below Montparnasse - Black, Cara, 1951- (Black, Cara, 1951- Aimée Leduc investigation, 2013)
Soloing the detective agency when her long-term partner leaves for a new job, Aimee is hired by a mysterious elderly Russian man to protect a valuable painting that is stolen before Aimee can start her work, a situation that is complicated by the client's murder and dangerous adversaries who also seek the painting.